Law Enforcement for Tax Reporters That Are Not Based On Actually Transactions through Electronic Taxes (E-Tax) - Eddy R (NAROTAMA UNIVERSITY, Indonesia, 2020)
This research is focused on aspects of law enforcement, especially in the area of tax law. In addition, the study examines the process of tax law enforcement which tends to emphasize criminal law rather than administrative law. This research was conducted using normative juridical methods which are based on primary legal materials. The results showed that emphasizing the criminal aspect in enforcing tax law would only jeopardize the main purpose of tax administration in collecting tax revenue that is very much needed for public spending. The results of this study are The tax law in Indonesia is regulated in Article 23A of the 1945 Constitution which reads: